(3EjVGM GdeSGdc Edi bhGYO GdEeGe eGdcs - (3CHh GdYHGS CMeO Hf jMji Hf eMeO Hf YHO GdhGMO Hf Ydj GdhfTQjSj,J (B914 (3g` s
(3ChdgG (B:s
(3hHYO aEfc SCdJfj CjgG GdaGVd GdTQja Cf CLeY dc JdNjUkG egPH GdaUhd, eMce GdeHGfj hGdCUhd s
(3BNQgG (B:s
(3hgh GdeSFhd SHMGfg hJYGdi Cf jUd ENhJce GdcQjeI hGdMeO ddg QH GdYGdejf s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B269s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B209s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQGdcJH (B- (3GdbGgQI (B((3abg eGdc T (B15) s
Keywords: (3Gdabg GdeGdcjs